(untitled) (Future Cities and Environment, 2025)
This study aimed to assess greenhouse gas (GHG) emissions at Rajamangala University of Technology Thanyaburi (RMUTT) and to propose strategies for transitioning towards a low-carbon university. The assessment combined three established scopes of GHG emissions, with data collected through 400 questionnaires distributed to students and staff to assess their awareness of low-carbon development and the possibility of implementing GHG reduction policies. Results indicated that Scope 2 emissions, primarily from electricity consumption, account for the largest share at approximately 7,527.05 tCO₂eq/year, followed by Scope 3 emissions at 2,577.92 tCO₂eq/year and Scope 1 emissions at 256.35 tCO₂eq/year, totaling 10,361.32 tCO₂eq/year. The average GHG emissions per person were estimated at 0.38–0.56 tCO₂eq/year. Using the rate-based target method, a 10% reduction in GHG emissions by 2030, in association with Thailand’s carbon neutrality goals, is projected to reduce total emissions to 3,612.18 tCO₂eq/year. Currently, carbon storage is expected to increase from 953.56 tCO₂eq/year to 1,929.70 tCO₂eq/year over a 10-year period, with 2032 as the target. Tree planting is identified as a cost-effective strategy for CO₂ removal; however, it should be complemented by additional mitigation measures informed by stakeholders’ perspectives on low-carbon university development. Achieving RMUTT’s transformation into a low-carbon institution requires technological advancements and policy reforms that foster sustainable practices and active stakeholder engagement. This study highlighted the importance of assessing and reporting GHG emissions as an essential step for institutions aiming to become sustainable organizations.